Characterisation of excavated plastics for thermochemical upcycling to platform chemicals and liquid fuels - Canopoli, Luisa; Fidalgo Fernandez, Beatriz; Wagland, Stuart T. (Cranfield University, 2018)
In Europe there are ~500,000 landfills; plastics represent a consistent and significant proportion of waste in landfill (typically 5-25% w/w). This fraction remains in the landfill, along with other non-biodegradable materials, long after the readily biodegradable organics have degraded. During storage in landfill the plastics physicochemical structure is likely to change because of the occurrence of chemical and biochemical reactions, which can lead to their degradation. For instance, H2S and organic acids produced during the acetogenesis phase of landfill are known to degrade plastics, therefore it can be hypothesised that plastics excavated from landfill are not suitable for conventional recycling. The fate of plastics in landfill has not been largely investigated and limited data exists addressing the changes in chemical and physical properties. The aim of this work is to investigate the degradation of plastics in landfill by characterising chemical and physical properties of samples excavated from different landfill depths. Waste samples were extracted from landfills across the UK at depths of 5-40 m. These were sorted in order to determine the total plastic content and the percentage of each type of plastic present (i.e. PET, HDPE etc). The types of plastics were identified using near infrared [NIR] spectroscopy. The surface properties of the excavated plastics were characterised using SEM/EDS to analyse and evaluate their degradation and contamination levels. Chemical characterisation of each plastic fraction has been carried out by proximate and ultimate analyses. Finally, the surface contamination (metal content) of the plastics was determined by ICP. Fresh, non-landfilled, plastic samples matching the plastic types of those found in landfill were characterised for comparison. The data highlighted plastic type variation across the samples, largely dependent on the age of the excavated material. The extent of degradation, was found to depend on the type of plastic and depth of the sample. This work contributes to address the potential utilisation of excavated plastics, such as for upcycling to platform chemicals and/or liquid fuels through thermochemical conversion.